Update on Acute Kidney Injury in Pediatrics- Part 1 - Hooman, Nakysa; Nakhaii, Shahrbanoo; Sharif, Mohammad –Reza (Journal of Pediatric Nephrology, 2014)
Acute kidney injury is known as an acute reversible insult to the kidney but its definition and classification is not uniform. Earlier classification of acute renal failure was according to pre-renal, renal, and post renal by using history, the time of response to fluid therapy, and some blood and urinary parameters and markers. Recently, efforts have been made to present a uniform definition of acute kidney injury for earlier disease detection in order to decrease the rate of morbidity, mortality, length of hospital stay, and even death. However, it is clear that serum creatinine is a late marker of renal injury and many new investigations have tried to find more sensitive biomarkers to recognize earlier stages of AKI, its exact underlying mechanism, and outcome. Here we provide the first section of a series about new concepts on AKI with focus on pediatrics. Keywords: Acute Kidney Injury; Pediatrics; Biological Markers; Classification.